Comorbid posttraumatic stress disorder and alcohol use disorder in low- and middle-income countries: A narrative review - Debra L. Kaysen; Katherine van Stolk-Cooke; Debra Kaminer; M. Claire Greene; Teresa López-Castro; Jeremy C. Kane (Cambridge Prisms: Global Mental Health, 2023)
Much of the research on posttraumatic stress disorder (PTSD) and alcohol use disorder (AUD) has been conducted in high-income countries (HICs). However, PTSD and AUD commonly co-occur (PTSD + AUD) are both associated with high global burden of disease, and disproportionately impact those in low- and middle-income countries (LMICs). This narrative review attempts to synthesize the research on prevalence, impact, etiological models, and treatment of PTSD + AUD drawing from research conducted in HICs and discussing the research that has been conducted to date in LMICs. The review also discusses overall limitations in the field, including a lack of research on PTSD + AUD outside of HICs, issues with measurement of key constructs, and limitations in sampling strategies across comorbidity studies. Future directions are discussed, including a need for rigorous research studies conducted in LMICs that focus on both etiological mechanisms and on treatment approaches.